Quelles conceptions de la réflexivité dans l’écriture de recherche? Savoir de quel je on parle - Françoise Boch (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The article is a literature review devoted to the enunciative positioning as the subject in research writing in the humanities, considered here from the angle of reflexivity. The general objective is to present a set of relevant work on this broad and polysemous concept in several disciplines. The article explores different ways of considering reflexivity in research writing and studies how these different theoretical conceptions can contribute to the reflection on the enunciative positioning of doctoral students in their thesis. It summarizes the ways these positions are symbolized by the first-person singular pronoun “I”.